Respuesta :

cheap answer, to get the x-intercepts, set x = 0 and solve for "y", to get the y-intercept, set y = 0 and solve for "x".

[tex]y-6=4(x+5) \\\\[-0.35em] ~\dotfill\\\\ y-6=4(\stackrel{x}{0}+5)\implies y-6=20\implies y=26~\hfill \stackrel{y-intercept}{(0~~,~~26)} \\\\[-0.35em] ~\dotfill\\\\ \stackrel{y}{0}-6=4(x+5)\implies -6=4x+20\implies -26=4x \\\\\\ \cfrac{-26}{4}=x \implies -\cfrac{13}{2}=x\implies -6\frac{1}{2}=x ~\hfill \stackrel{x-intercept}{\left( -6\frac{1}{2}~~,~~0 \right)}[/tex]

ACCESS MORE